Effect of vitamin supplementation on the ingestive, digestive, and ruminal parameters of Nellore cattle - Silva, Júlia Travassos da (2020)
Rumen cannulated Nellore bulls (n = 4) were used in a 4 × 4 Latin square design to evaluate the effects of vitamin supplementation on 1) ingestive, digestive, and ruminal parameters; 2) serum concentrations of 25-hydroxyvitamin D (25(OH)D); and 3) in situ degradability of complete diets. The following treatments were applied: No vitamin supplementation (CTL), supplementation of a B vitamin blend (biotin, niacin, and thiamine; Vit B blend), supplementation with a fat-soluble vitamin blend (Vit ADE), or a combination of these two blends (Vit B blend+ADE) . The basal diet (30:70 roughage:concentrate ratio) was formulated to achieve an average daily gain of 1.2 kg/day. Vitamin blends were premixed into the concentrate and the levels of each vitamin per kg of DM were: 3.3 mg of biotin, 111.1 mg of niacin, 28.9 mg of thiamine, 6666.7 IU of vitamin A, 5111.1 IU of vitamin D 3 , and 70 IU of vitamin E. Each experimental period lasted 25 days, with 14 days of adaptation to the diets and 11 days for data collection. Dry matter and nutrient intake, as well as ruminal, intestinal, and total-tract digestibility, were not affected (P ≥ 0.072) by any of the vitamin supplementations. Further, the treatments did not affect ruminal kinetics (omasal flow (g/d) of total N, NH 3 -N, Non ammonia N, microbial N, and Non ammonia non microbial N) (P ≥ 0.234), the efficiency of microbial protein synthesis (P ≥ 0.197) and nitrogen balance (P ≥ 0.228). Ruminal parameters (pH, NH 3 -N, individual and total fat volatile acids (VFA) concentration) were not affected (P ≥ 0.133) by vitamin supplementations. As expected, concentrations of serum 25(OH)D increased (P = 0.001) in Nellore bulls fed diets with Vit ADE and Vit B blend+ADE supplementation. None of the in situ parameters (readily soluble fraction, potentially degradable fraction in the rumen (b) or in the rate constant for degradation of b) were affected (P ≥ 0.434) by vitamin supplementation. In conclusion, supplementing Nellore bulls with 25(OH)D 3 was a successful strategy for increasing circulating concentrations of 25(OH)D. However, supplementation of a B-vitamin blend, a fat-soluble vitamin blend, or a combination of these two blends in high concentrate-diets did not improve ruminal fermentation, in situ degradability of complete diets, ingestive and digestive parameters in Nellore bulls. Keywords: B vitamin. Fat-soluble vitamin. Digestibility. Rumen.